2019
DOI: 10.1111/jcmm.14554
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T cells protected against abdominal aortic aneurysm by suppression of the COX‐2 expression

Abstract: CD4+CD25+ regulatory T cells (Tregs) have been shown to protect against the development of abdominal aortic aneurysm (AAA). Cyclooxygenase‐2 (COX‐2), a pro‐inflammatory protein, can convert arachidonic acid into prostaglandins (PGs). The present study was aimed to investigate the effect of Tregs on COX‐2 expression in angiotension II (Ang II)‐induced AAA in ApoE−/− mice. Tregs were injected via tail vein in every 2 weeks. Ang II was continuously infused by a micropump for 28 days to induce AAA. In vivo, compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…An array of different inflammation modifying regimens have recently been reported to inhibit or promote the incidence and/or rupture of AAAs formed in the different mouse models (Figure 2 and Table S1) (Amin et al, 2019;Hiromi et al, 2020;Krishna et al, 2019;Li, Nie, et al, 2019;Li, Xia, et al, 2019;Liu, Fitzgerald, et al, 2019;Liu, Kong, et al, 2019;Nie et al, 2019;Paige et al, 2019;Peshkova et al, 2019;Ren et al, 2020;Sharma, Dev, Belenchia, et al, 2019;Suehiro et al, 2019;Suh et al, 2020). The nucleotide-binding domain leucine-rich repeat (NLR) and pyrin domain-containing receptor 3 (NLRP3)-inflammasome plays an important role in innate immunity through controlling the secretion of pro-inflammatory cytokines.…”
Section: Assessing Outcomes In Mouse Models Of Aaamentioning
confidence: 99%
See 2 more Smart Citations
“…An array of different inflammation modifying regimens have recently been reported to inhibit or promote the incidence and/or rupture of AAAs formed in the different mouse models (Figure 2 and Table S1) (Amin et al, 2019;Hiromi et al, 2020;Krishna et al, 2019;Li, Nie, et al, 2019;Li, Xia, et al, 2019;Liu, Fitzgerald, et al, 2019;Liu, Kong, et al, 2019;Nie et al, 2019;Paige et al, 2019;Peshkova et al, 2019;Ren et al, 2020;Sharma, Dev, Belenchia, et al, 2019;Suehiro et al, 2019;Suh et al, 2020). The nucleotide-binding domain leucine-rich repeat (NLR) and pyrin domain-containing receptor 3 (NLRP3)-inflammasome plays an important role in innate immunity through controlling the secretion of pro-inflammatory cytokines.…”
Section: Assessing Outcomes In Mouse Models Of Aaamentioning
confidence: 99%
“…A large body of published research suggests that Foxp3 + regulatory T cells inhibit AAA development within both the angiotensin II and CaCl 2 models (Golledge, 2019;Liu, Kong, et al, 2019;Suh et al, 2020;Yodoi et al, 2015). Of potential clinical application, it was recently reported that ex vivo expansion and administration of Foxp3 + regulatory enriched T cells reduced the size of CaCl 2 -induced AAAs (Suh et al, 2020).…”
Section: Assessing Outcomes In Mouse Models Of Aaamentioning
confidence: 99%
See 1 more Smart Citation
“…[ 9 ] Notably, alteration of AII receptors or/and the down‐stream signaling could increase the risk in many important processes underlying vascular injury in cardiovascular diseases. [ 10–14 ] Therefore, AII was used to test the basic vascular function in the present study. Ca 2+ is an important factor to regulate vascular contractions following stimulation of AII.…”
Section: Introductionmentioning
confidence: 99%
“…Ruptures are fatal in 80% of cases and associated with extreme disability if survived [19]. No specific pharmacological treatment is available during the asymptomatic stage, although COX-2 inhibitors could be expected to have some effect on aneurysm growth and in preventing or delaying wall dissection [20,21]. The inventors have shown increased expression of tyrosine hydroxylase (the rate-limiting enzyme in catecholamine synthesis) in samples of patients with abdominal aortic aneurysm.…”
mentioning
confidence: 99%